The Relevance of Bourdieu’s Theory in Examining The Dynamics of Social Practices in Malang Thematic Villages: Sapa Sing Duwe Modal, Sapa Sing Bisa Urip - Khansa Qani'ah Khairunnisa; Danica Fazilla Umri Nasution; Patta Hindi Asis (Journal of Southern Sociological Studies, 2025)
This article examines how Pierre Bourdieu's theory of social practice, focusing on habitus, capital, and field, can be applied to analyze the dynamics of success and failure in the development of thematic villages in Malang City. The study uses Kampung Biru Arema and Kampung Putih as case studies to understand how community social practices are shaped and constrained by the distribution of social, cultural, economic, and symbolic capital within the tourism development field. It also examines how habitus, formed through past life experiences, influences the community's capacity to respond to thematic village initiatives. Using a qualitative approach through literature review and field observation, the study finds that top-down development interventions do not automatically lead to sustainable change when there is no balanced exchange of capital between external actors and residents. In both cases, the communities lacked sufficient social and cultural capital to manage tourism independently, and the development field failed to provide a reflective space for building a new habitus aligned with their roles as tourism actors. A reflection on Bourdieu's theory suggests that the failure of social transformation in thematic villages is not merely due to weak policy structures, but also because social practices lack adequate capital to compete in a new field. This study emphasizes the need to consider power relations and capital distribution in community-based tourism development so that initiated programs are symbolic and rooted in sustainable social practice.